Lost : miscarriage in nineteenth-century America - Withycombe, Shannon (Critical issues in health and medicine., 2019)
In Lost, medical historian Shannon Withycombe weaves together women's personal writings and doctors' publications from the 1820s through the 1910s to investigate the transformative changes in how Americans conceptualized pregnancy, understood miscarriage, and interpreted fetal tissue over the course of the nineteenth century. Withycombe's pathbreaking research reveals how Americans construed, and continue to understand, miscarriage within a context of reproductive desires, expectations, and abilities. This is the first book to utilize women's own writings about miscarriage to explore the individual understandings of pregnancy loss and the multiple social and medical forces that helped to shape those perceptions. What emerges from Withycombe's work is unlike most medicalization narratives.